The Influence of APBD Plans and APBD Realization on Economic Growth (Empirical Study of Brebes Regency for the 2018-2022 Period) - Roseniati, Irna; Kharisma, Anisa Sains; Roni, Roni (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
This study aims to determine and analyze the effect of the APBD plan, realization. This study aims to determine and analyze the influence of the APBD plan, APBD realization on the economic growth of Brebes Regency. This research takes an empirical study in Brebes Regency in the 2018-2023 period. This is related to a plan and realization that cannot be separated in a process of the APBD cycle which will affect regional income and expenditure so that the use is in accordance with welfare needs and existing provisions. With the existence of the APBD, it is hoped that it will be able to increase income which will affect GRDP which will affect economic growth. The population used is the report on the realization of the Brebes Regency APBD in 2018 to 2022 using the non-probability sampling technique found in the APBD realization report relating to income and expenditure reports. The data used is secondary data taken by LRA and GRDP. Statistical analysis of data using the SPSS program with multiple linear regression analysis tools. The results showed that partially APBD planning and APBD realization had a positive and significant effect on economic growth with the APBD planning results t count 2.068 t table 4.302, and APBD realization t count -1.988 t table -4.302, with degrees α = 0.025. And to simultaneously have no effect on the results of the analysis F count 2.420 F table 10.13. So that partially the APBD plan has a partial and significant effect on economic growth, the realization of the APBD has a partial and significant effect on economic growth. And simultaneously the APBD plan and APBD realization have no effect on economic growth.